Antiviral Activity of Fridericia formosa (Bureau) L. G. Lohmann (Bignoniaceae) Extracts and Constituents - Geraldo Célio Brandão; Erna G. Kroon; José D. Souza Filho; Alaíde Braga Oliveira (Journal of Tropical Medicine)
A phytochemical study of Fridericia formosa (Bignoniaceae) ethanol extracts of leaves, stems, and fruits was guided by in vitro assays against vaccinia virus Western Reserve (VACV-WR), human herpes virus 1 (HSV-1), murine encephalomyocarditis virus (EMCV), and dengue virus type 2 (DENV-2) by the MTT method. All the ethanol extracts were active against DENV-2, HSV-1, and VACV-WR with best results for the fruits extract against DENV-2 (SI > 38.2). For VACV-WR and HSV-1, EC50 values > 200 μg mL−1 were determined, while no inhibition of the cytopathic effect was observed with EMCV. Five compounds were isolated and identified as the C-glucosylxanthones mangiferin (1), 2′-O-trans-caffeoylmangiferin (2), 2′-O-trans-coumaroylmangiferin (3), 2′-O-trans-cinnamoylmangiferin (5), and the flavonoid chrysin (4). The most active compound was 2′-O-trans-coumaroylmangiferin (3) with SI > 121.9 against DENV-2 and 108.7 for HSV-1. These results indicate that mangiferin cinnamoyl esters might be potential antiviral drugs.